2017
DOI: 10.1126/sciadv.1601576
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between protein glycosylation pathways in Alzheimer’s disease

Abstract: Glycome analysis of Alzheimer’s patients reveals interplay between glycosylation pathways and suggests novel biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 57 publications
1
66
0
Order By: Relevance
“…Many additional potential nucleators of Aβ aggregation have been suggested, not always with well formulated mechanisms. ApoE, [181][182][183] collagens and collagen-related proteins, [184][185][186][187][188] and extracellular matrix glycans, [189][190][191][192][193][194] among other molecules have all been suggested as sites at which Aβ aggregation might begin. Such suggestions in no way diminish the importance of metal ions or membrane lipids but add to the potential complexity of the process.…”
Section: Metal Ionsmentioning
confidence: 99%
“…Many additional potential nucleators of Aβ aggregation have been suggested, not always with well formulated mechanisms. ApoE, [181][182][183] collagens and collagen-related proteins, [184][185][186][187][188] and extracellular matrix glycans, [189][190][191][192][193][194] among other molecules have all been suggested as sites at which Aβ aggregation might begin. Such suggestions in no way diminish the importance of metal ions or membrane lipids but add to the potential complexity of the process.…”
Section: Metal Ionsmentioning
confidence: 99%
“…Besides, aberrant levels of O-GlcNAc has been reported also on APP implying that this modification could be involved in the induction of its nonamyloidogenic processing by γ-secretase and to the formation of senile plaques [12]. Noteworthy, recent studies reported that the reduction of protein O-GlcNAcylation in AD and tau-driven pathologies do not occurs indiscriminately in all the brain proteome but it appears to vary between brain regions and a specific subcellular fraction of the neurons [13].…”
Section: Protein O-glcnacylation and Tauopathiesmentioning
confidence: 99%
“…Nucleotide sugars serve as building block for glycoproteins, glycolipids and glycosylphosphatidylinositol anchors. These complex glycoconjugates are involved in important biological processes such as cellular communication and signaling and have been associated with numerous human diseases, both acquired [1][2][3][4] and genetic. [5] Disruptions in sugar metabolism have been linked to various diseases such as cancer, [6] neurodegenerative [7] and infectious [8] disease, some of them being treatable via dietary intervention in sugar metabolism like galactose supplementation in PGM1 myopathy.…”
Section: Introductionmentioning
confidence: 99%